The AMAL Program : "Hope" for Unemployed Youth in the MENA Region - Angel-Urdinola, Diego F.; Leon-Solano, Rene (World Bank, Washington, DC, 2012)
To respond to high unemployment rates among youth (often educated entrants to the labor market), many countries in the Middle East and North Africa (MENA) region have designed and implemented programs that aim to enhance youth employability. However, a recent study revealed that despite significant investments, many youth programs in MENA lack the necessary features that make these types of programs successful. This note describes a new approach to youth employment programs in MENA through the recently implemented AMAL (Arabic for 'Hope') program in Tunisia. AMAL is the first large-scale publicly financed comprehensive youth program in the region. If well-implemented and carefully evaluated, AMAL could become a building block for a comprehensive reform of youth employment programs in the region. This note starts with an overview of international best practices for the design/implementation of youth programs. The note provides a brief description of youth programs in Tunisia and mainly of the AMAL program, highlighting some of its main challenges and opportunities. The World Bank supported the Interim Government of Tunisia in the design and implementation of the AMAL program through the Governance and Opportunities Development Policy Loan (DPL), a multi-sector program of reforms that supports the post-revolution transition period.